Time of breeding and female condition affect chick-growth in the Chilean Swallow (Tachycineta meyeni) - Liljesthrom, Marcela (2012)
We analysed growth of nestling Chilean Swallows (Tachycineta meyeni) over four consecutive breeding seasons and determined the factors that explain variation in growth rate, asymptotic body mass and length of the nestling period. As the breeding season advanced nestlings grew more slowly and attained lower asymptotic mass, but the length of the nestling period and nestling survival did not show any seasonal trend. Asymptotic body mass of nestlings increased with female body condition, which was negatively correlated with time of breeding, suggesting that a seasonal decline in asymptotic body mass could be the result of changes in environmental conditions or lower quality of females breeding later in the season. There was no relationship between average minimum ambient temperature and either growth rate or asymptotic mass during the nestlings first 10 days. However, short periods of poor weather and snowfall had a significant effect on nestling survival. Growth rate (0.43) was lower than that of other Tachycineta species nesting at similar latitudes in the northern hemisphere but similar to those of subtropical species of the genus, suggesting that the factors that have influenced the evolution of this life-history trait differ between Chilean Swallows and other species of Tachycineta.